2018
DOI: 10.51200/jkob.v0i0.1578
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Effect of the Islamic Religious Personality on the Relationship between the Islamic Worldview and Intercultural Sensitivity among Students

Abstract: Muslims consider themselves to be a ‘family of believers’ (Samovar, 2009) as Islam emphasizes the importance of perceiving and treating other Muslims beyond the differences of appearance and culture. This study examines the relationships of the Islamic worldview and Islamic religious personality with intercultural sensitivity, as well as the mediating effect of the Islamic religious personality on the relationship between the Islamic worldview and intercultural sensitivity in an international learning inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Albehairi & Demerdash, 1988;Sateemae et al, 2015) have suggested that in general, females tend to display greater religious impulses than males. Noorfuad and Wok (2018) assessed the relationship between religiosity and intercultural sensitivity and found a positive correlation between the two.…”
Section: Religiositymentioning
confidence: 99%
“…Albehairi & Demerdash, 1988;Sateemae et al, 2015) have suggested that in general, females tend to display greater religious impulses than males. Noorfuad and Wok (2018) assessed the relationship between religiosity and intercultural sensitivity and found a positive correlation between the two.…”
Section: Religiositymentioning
confidence: 99%